Survey of preweaning dairy calf-rearing practices in Czech dairy herds - Staněk, S; Zink, V; Doležal, O; Štolc, L (Journal of dairy science, 2014)
It is important to describe weaknesses in rearing calves not only to improve their welfare, but also to detect areas where current scientific knowledge is poorly integrated into practice. A survey of preweaning calf-rearing practices was conducted using a farmer questionnaire. The survey included 136 farms, representing 11.9% of all dairy cows in the Czech Republic. Mean herd size (± standard deviation) was 326 ± 131.4 cows, and mean milk production 7,413 ± 1,389.5 kg per cow per year. We evaluated 59 farms with Holsteins (H) and 77 with the Czech Fleckvieh breed (C). The survey revealed that (1) calving in group pens predominated (67.6% of farms); (2) no disinfection of calf navels occurred on 11.8% of herds; (3) pooled colostrum was fed on 15.4% of farms; (4) colostrum quality was controlled on only 44.1% of farms, and only 73.5% of farms had reserve colostrum stocks; (5) nonmarket waste milk was fed in 64.7% of herds but it was pasteurized in only in 6.8% of herds and acidified in 35.2% of herds; (6) milk replacer was mixed with nonmarket waste milk on 52.9% of farms; (7) 58.8% of farms enabled calves to obtain milk by sucking and 41.2% by drinking from a bucket; (8) the main criterion in weaning was calf age (61.7%), followed by acceptance of starter and concentrated feed (19.9%) and lack of housing capacity (18.4%); and (9) newborn calves were individually housed on 96.7% of farms and group-housed on 3.3% of farms. The most marked differences in calf-rearing management between Holstein and Czech Fleckvieh farms were (1) a higher proportion of operations calving in tie-stalls or stanchions in C (6.5%) versus H (1.7%) farms; (2) a higher proportion of untreated navels on C (15.6%) versus H (6.8%) farms; (3) a lower proportion of C (11.7%) versus H (20.4%) farms feeding pooled colostrum; (4) a lower proportion of C (39%) versus H (50.9%) farms monitoring colostrum quality; (5) sucking milk from nipple buckets predominated (61%) on C farms, whereas drinking from an open bucket was most common (64.4%) on H farms; (6) age was the main criterion in weaning calves of both breeds (C farms: 55.8%, H farms: 69.5%), whereas the second most important criterion was lack of housing capacity (28.6% of farms) on C farms and the amount of consumed starter (25.4%) on H farms. We observed a difference in duration of colostrum period between C herds (median 5d) and H herds (median 4d). A tendency was observed for age of calves at weaning (C herds: median at 9.1 wk, H herds: median at 10 wk).
Keywords: rearing; welfare; Male; Česká republika; Dairying; mužské pohlaví; farm management; skot; Czech Republic; Weaning; ženské pohlaví; zvířata; mlékárenství; Cattle; rizikové faktory; odstavení; Female; Risk Factors; calf; Animals